Hydrothermal synthesis of SnO2/cellulose nanocomposites: optical, Structural, and morphological characterization - Y. C. Goswami; R. Bisauriya; Ranjana Goswami; A. A. Hlaing; T. T. Moe (Scientific Reports)
Abstract This study details the hydrothermal synthesis and characterization of SnO2/nanocellulose (NC) nanocomposites, highlighting their potential for advanced applications. X-ray diffraction (XRD) analysis confirmed the amorphous nature of the composites, with a broad peak at 25.6° and a rightward shift indicating strong SnO2-NC interactions. A sharp peak at 32.26° in the SnO2-20 sample signified a rutile structure with single-plane crystallinity. UV-Vis absorption spectra showed a significant blue shift, with bandgap values reaching 5.86 eV for SnO2-5, compared to 3.6 eV for pure SnO2, demonstrating enhanced optical properties. Photoluminescence (PL) spectra revealed prominent emissions at 384 nm and 486 nm, attributed to oxygen vacancies and defect states, which enhance luminescence and support optoelectronic applications. FTIR spectroscopy identified a peak at 3430 cm−1, confirming abundant hydroxyl groups on cellulose surfaces and high sample purity. Scanning electron microscopy (SEM) images showed uniformly distributed SnO2 nanoparticles on an amorphous NC matrix, with rod-like features contributing to irregular morphologies that impact defect density and optical behavior. These structural and optical improvements enhance charge transport and reduce carrier recombination, establishing SnO2-NC nanocomposites as promising materials for optoelectronic devices, gas sensors, and photocatalysis. The integration of eco-friendly nanocellulose offers a sustainable pathway for developing next-generation technologies with superior performance.